The Website Development for Blood Donation in Kazakhstan - Bulekbayeva, A.S. (International School of Economics Maqsut Narikbayev University, Astana, 2024)
The subject of blood donation was examined using differentiated techniques in many of countries being primarily founded on analysis of population perception. This research aims to investigate the current state of blood donation procedure in Kazakhstan for proposal of a digital solution as a web application to anticipate an improvement of existing system for medical institutions and blood donors. The objective of the study dedicated to analysis of existing framework required for successful adoption of the website. The study based upon primary data arose from an interview with the Blood Center executive of Astana followed with anonymized digital survey and the website development analysis. The results suggest that a digital platform dedicated to transfusion medicine have potential to be efficient environment for Blood Centers for such strategies as collection of donors and promotion of a matter as blood donation. The research extends the literature on digitalization in the context of web development for healthcare facilities.
Keywords: Blood donation, Transfusion medicine, Blood donors, Blood Center, Website